2004
DOI: 10.1097/01.ccm.0000126895.66850.14
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in End-of-Life Care in the ICU: Statement of the 5th International Consensus Conference in Critical Care: Brussels, Belgium, April 2003: Executive Summary

Abstract: Strong recommendations for research to improve end-of-life care were made. The jury advocates a shared approach to end-of-life decision-making involving the caregiver team and patient surrogates. Respect for patient autonomy and the intention to honor decisions to decline unwanted treatments should be conveyed to the family. The process is one of negotiation, and the outcome will be determined by the personalities and beliefs of the participants. Ultimately, it is the attending physician's responsibility, as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(87 citation statements)
references
References 11 publications
0
83
0
1
Order By: Relevance
“…We did not know what proportion of the do-not-resuscitate orders in this study were related to an advance directive by the patient. However, previous reports have showed that only 10% of ICU patients have prepared an advanced directive (35), and almost one half of do-not-resuscitate orders are written within 2 days of death (36). Therefore, the effect of advanced directives on our findings is likely small.…”
Section: Discussionmentioning
confidence: 99%
“…We did not know what proportion of the do-not-resuscitate orders in this study were related to an advance directive by the patient. However, previous reports have showed that only 10% of ICU patients have prepared an advanced directive (35), and almost one half of do-not-resuscitate orders are written within 2 days of death (36). Therefore, the effect of advanced directives on our findings is likely small.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for patients with significant life-altering comorbidities, mortality may not be the most important patient-centered outcome. Patients and families frequently express a wish for aggressive ICU treatment if a return to an independent existence is possible but opt for comfort measures if the outcome is likely to be a further diminution in independent quality of life (64,65).…”
Section: Does It Help?mentioning
confidence: 99%
“…Because patients are most often too ill to participate, surrogates are asked to make choices based on what their loved one would want. 2,3 Concerns have been raised about the extent to which current approaches to decision making place undue strain on families and lead to decisions that do not accurately reflect patient values. [4][5][6] A recent systematic review found that at least one third of surrogates report negative emotional effects lasting months, and sometimes years, after making treatment decisions for others, including stress, guilt and doubt about whether they made the right choice.…”
Section: Introductionmentioning
confidence: 99%